Strengthening South-South Cooperation: Indonesia’s Grant to Afghanistan in 2022 - Suhafid, Muh. Zulhamdi; Zainal, Nur Aliyah; Darussalam, Miftah Farid (Intermestic: Journal of International Studies, 2025)
This research aims to analyze the implementation of Indonesia's grant program for Afghanistan in 2022 as a manifestation of strengthening South-South cooperation. By exploring using the constructivism approach in international relations related to the identity and interests of the two countries, it forms a pattern of bilateral cooperation. The research used qualitative method with data collection techniques through journals and reports on strengthening South-South cooperation through grant programs. The results showed that the grant program was allocated into three priority sectors: Handling the Food Crisis, Capacity Building Training in Maternal and Child Health, and Educational Support Assistance for Afghan Postgraduate Students. The program successfully trained and improved the academic skills of Afghans, increased agricultural productivity in targeted areas and access to basic health services. While this cooperation has faced challenges, Indonesia's adaptive approach through cooperation with local organizations and the use of information technology for remote monitoring has proven effective. This study concludes that the success of the grant program not only strengthens bilateral relations but also shows the strengthening of state-identity solidarity in the south-south region, which emphasizes equality, care, and the encouragement of identity among Muslim-developing countries.